(untitled) (Research, Society and Development, 2021)
Objective: The aim of this study was to evaluate the size, shape and location of the mental foramen (MF) and anterior loop (AL) in the Brazilian population through the analysis of cone beam computed tomography (CBCT) and panoramic radiography (PR). Method: We analyzed the location, shape and size of the MF, the distance between the upper wall of the MF and the alveolar crest (AC), the size of the AL and the presence of lingual anastomosis. Results: Fifty PR and CBCT exams were analyzed. In relation to the MF, the most common location was between premolars (56%), the most common shape was the oval shape (83%) and the average size in the PR was 3.63 mm and in the CBCT was3.66 mm. The average distance from the MF to the AC in the PR was 17.29 mm and in the CBCT was 11.48 mm. The average AL size was 3 mm, the smallest being 1 mm and the largest being 5 mm. Static analysis was performed to verify the relationship between the distance from the foramen to the AC with the values ​​that were found in the PR and CBCT, which showed a statistically significant difference (p=<0.001) between them. Lingual anastomosis could be seen in 22% of the analyzed hemimandibles. Conclusion: CBCT is a reliable diagnostic test for planning rehabilitation near the MF. The distance between the implant and the foramen must be analyzed individually.